Synthesis and Characterization of MgO Thin Films Obtained by Spray Technique for Optoelectronic Applications - Maher Tlili (MDPI AG, 2021)
Magnesium oxide (MgO) thin films with different magnesium concentrations ([Mg2+] = 0.05, 0.1, 0.15 and 0.2 mol·L−1) in a spray solution have been successfully grown using a spray pyrolysis technique. X-ray diffraction (XRD), Maud software, FTIR spectroscopy, a confocal microscope, Wien2k software, spectrophotometry and a Photoluminescence spectrometer were used to investigate the structural, morphological and optical properties. XRD analysis revealed a better crystalline quality of the MgO thin layer synthesized with [Mg2+] = 0.15 mol·L−1, which crystallized into a face-centered cubic structure along the preferred orientation (200) lattice plan. The enhancement of the crystalline quality for the MgO thin film ([Mg2+] = 0.15 mol·L−1) was obtained, which was accompanied by an increment of 94.3 nm of the crystallite size. No secondary phase was detected and the purity phase of the MgO thin film was confirmed using Maud software. From the transmission spectra results, high transparent and antireflective properties of the MgO thin film were observed, with an average transmission value of about 91.48% in the visible range, which can be used as an optical window or buffer layer in solar cell applications. The films also have a high reflectance value in the IR range, which indicates that the highly reflective surface will prevent an increase in surface temperature under solar irradiation, which could be beneficial in solar cell applications. A direct band gap type was estimated using the Tauc relation which is close to the experimental value of 4.0 eV for optimal growth. The MgO material was tested for the degradation of methylene blue (MB), which reached a high photodegradation rate of about 83% after 180 min under sunlight illumination. These experimental trends open a new door for promising the removal of water contaminants for photocatalysis application.